The State of the Intestinal Microflora in Hospitalized Children with Acute Intestinal Infections - Z. M. Kuliyeva; L. I. Rustamova; S. M. Faradzheva; M. G. Aliev; I. B. Israfilbekova; M. N. Mamedova; S. F. Suleymanova; F. V. Gylyndzhova (LLC "Diagnostics and Vaccines", 2018)
The purpose of this study was to study the state of the intestinal microflora in young children who received inpatient treatment for acute intestinal infections. A study of the microflora in 183 children aged 0 months. up to 3 years of life. At the same time, 43 (23.5%) children received breast milk, 53 (29.0%) were artificially fed and 87 (47.5%) mixed-fed children. All children were examined by bacteriological method. Conditionally pathogenic flora among hospitalized patients was detected in 114 (62.3%), Candida was mainly detected in 67.5% of cases, in 57 patients (50.0%) in association with other opportunistic microorganisms - Candida + St. aureus - in 32 (28.1%), Candida + P. vulgaris - in 9 (7.9%), Candida + + P. vulgaris + St. aureus - in 12 (10.5%), Candida + St. aureus + Ps. aeroginosa - in 4 (3.5%). As a result of studying the composition of the intestinal microflora in patients hospitalized with intestinal infection, a decrease in the number of E. coli and B. bifidum was found, 43.7% and 63.4%, respectively.